Inhibitory targeting cGAS-STING-TBK1 axis: Emerging strategies for autoimmune diseases therapy - Zhang, Min; Zou, Yan; Zhou, Xujun; Zhou, Jinming (Frontiers in Immunology, 2022)
The cGAS-STING signaling plays an integral role in the host immune response, and the abnormal activation of cGAS-STING is highly related to various autoimmune diseases. Therefore, targeting the cGAS-STING-TBK1 axis has become a promising strategy in therapy of autoimmune diseases. Herein, we summarized the key pathways mediated by the cGAS-STING-TBK1 axis and various cGAS-STING-TBK1 related autoimmune diseases, as well as the recent development of cGAS, STING, or TBK1 selective inhibitors and their potential application in therapy of cGAS-STING-TBK1 related autoimmune diseases. Overall, the review highlights that inhibiting cGAS-STING-TBK1 signaling is an attractive strategy for autoimmune disease therapy.